A 61-year-old man with Lichen Simplex Chronicus, Rosacea, CVA Sequelae, Stage II Hypertension, Class II Obesity, and Psychological Stress with risk factors of Unhealthy Diet and Damp Environment - Maharani, Aliyya; Kuntadi Syamsul Hidayat, Mohammad; Andarini, Sri (Jurnal Ilmu Kedokteran Keluarga, 2026)
Introduction: Neurodermatitis and rosacea are chronic dermatological conditions often triggered bypsychological and environmental factors. In patients with comorbid hypertension, obesity, and historyof stroke, management requires a holistic approach. Methods: A case report of a 61-year-old malewith complaints of itching on the left ankle and facial erythematous patches. Data were obtainedthrough history taking, physical and supporting examinations, as well as psychosocial and familyassessments. Results: The diagnoses established were neurodermatitis, rosacea, stage II hypertension,and CVA sequelae. The patient also presented with moderate anxiety based on the GAD-7 score.Comprehensive management included pharmacological therapy (topical hydrocortisone,antihypertensives, antiplatelet), non-pharmacological interventions (DASH diet, stress management,range-of-motion exercises), and family involvement to support adherence. After initial interventions,skin lesions improved and the patient reported better emotional control. Discussion: Family medicineprovides comprehensive care by integrating biomedical, psychological, social, and environmentalaspects. Family support plays a key role in improving treatment adherence and patient quality of life.Conclusion: This case emphasizes the importance of a multidimensional approach in family medicinefor patients with multiple chronic conditions.